Intranasal administration of exosomes derived from mesenchymal stem cells ameliorates autistic-like behaviors of BTBR mice - Nisim Perets; Stav Hertz; Michael London; Daniel Offen (2018)
Autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by three core symptoms that include social interaction deficits, cognitive inflexibility, and communication disorders. They have been steadily increasing in children over the past several years, with no effective treatment. BTBR T+tf/J (BTBR) mice are an accepted model of evaluating autistic-like behaviors as they present all core symptoms of ASD. We have previously shown that transplantation of human bone marrow mesenchymal stem cells (MSC) to the lateral ventricles of BTBR mice results in long lasting improvement in their autistic behavioral phenotypes. Recent studies point exosomes as the main mediators of the therapeutic effect of MSC. Here, we tested whether treatment with the exosomes secreted from MSC (MSC-exo) will show similar beneficial effects. We found that intranasal administration of MSC-exo increased male to male social interaction and reduced repetitive behaviors. Moreover, the treatment led to increases of male to female ultrasonic vocalizations and significant improvement in maternal behaviors of pup retrieval. No negative symptoms were detected following MSC-exo intranasal treatments in BTBR or healthy C57BL mice. The marked beneficial effects of the exosomes in BTBR mice may translate to a novel, non-invasive, and therapeutic strategy to reduce the symptoms of ASD.